Effect of Increasing the Level of a Modified Corn Protein on Nursery Pig Growth Performance, Feed Efficiency, and Fecal Dry Matter - Alan J. Warner; Jason C. Woodworth; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Jordan T. Gebhardt; Keith Mertz (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 360 barrows (DNA 200 × 400; initially 13.4 ± 0.12 lb) were used in a 38-d study to evaluate the effects of increasing levels of a modified corn protein product on nursery pig growth performance and fecal dry matter. Upon arrival to the nursery research facility, pigs were randomly assigned to pens (5 pigs per pen) and pens were allotted to 1 of 6 dietary treatments with 12 pens per treatment. Experimental diets were fed in two phases with phase 1 fed from d 0 to 10 and phase 2 fed from d 10 to 25. Phase 1 diets were formulated with 3, 6, 9, 12, and 15% of a modified corn protein or 6% enzymatically treated soybean meal (ESBM). The inclusion level of the test protein source and ESBM for the phase 2 diets were: 1.5, 3, 4.5, 6, 7.5, and 3%, respectively. A common phase 3 diet was fed from d 25 to 38. Phase 1 treatment diets were fed in pellet form, with phases 2 and 3 fed in meal form. During the phase 1 period, there was no evidence (P>0.10) for differences in ADG, ADFI, or F/G. There was a tendency (linear,P= 0.092) for increased d 10 BW as the level of the modified corn protein increased. From d 10 to 25 (phase 2 period), increasing the level of modified corn protein increased (quadratic,P= 0.037) d 25 BW, ADG (quadratic,P= 0.026) and ADFI (quadratic,P= 0.034). Feed efficiency worsened (linear,P= 0.063) with increasing levels of modified corn protein source. From d 0 to 25 (experimental period), ADG (quadratic,P= 0.030) and ADFI (quadratic,P= 0.036) increased, and F/G worsened (linear,P= 0.006). From d 25 to 38 (common period), there was no evidence (P>0.10) for differences in growth performance. For the overall experiment, ADG (quadratic,P= 0.028) and ADFI (quadratic,P= 0.032) increased then decreased, with pigs fed the intermediate inclusion of modified corn protein (6.0 and 3.0% in phases 1 and 2, respectively) having the best performance. There was also evidence (linear,P= 0.066) for F/G to worsen as the inclusion level of modified corn protein increased and this may be reflective of lower energy diets and/or overestimation of the energy value of the modified corn protein product. Fecal DM on d 25 tended to increase (quadratic,P= 0.051) as the level of the modified corn protein was increased, although no evidence of a difference (P>0.10) was observed between treatments on d 10. There was greater (P= 0.004) fecal DM on d 25 compared to d 10. These data suggest that the modified corn protein tested in this trial may be an alternative protein source to consider for nursery pig diets, when fed up to 12% in phase 1 and 6% in phase 2. Additional research should be conducted to confirm the energy value of the modified corn protein product utilized in this study.
Keywords: amino acid source; corn protein; growth; nursery pig